(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study estimated the profitability, farm specific technical efficiency of lentil growers and measured the impacts of different factors associated with technical efficiency of lentil farmers. The study employed farm level cross sectional data from three lentil growing districts namely Jessore, Meherpur and Natore of Bangladesh. The study revealed that HYV lentil is profitable than local variety. Cost of human labour, organic fertilizer, TSP, MoP and irrigation cost were found to contribute significantly in the efficiency of lentil farmers. The average technical efficiency of lentil growers in Bangladesh is 64 percent. This indicates a good potential for increasing lentil output by 36 percent with the existing technology and level of inputs. Farmers’ educations and training have positive significant effect on yield and efficiency of lentil production. Farmers faced some problems like disease infestation, lack of storage facilities, lack of knowledge, untimely rainfall, high price of input and unavailability of HYV seed. Therefore, researchers should develop integrated pest, disease and insect management schedule which are environment friendly and ecologically sound. Good quality seeds of lentil should be made available locally to the farmers at a reasonable price. Bangladesh J. Agril. Res. 43(1): 135-147, March 2018